A novel micromechanical-based secant method to predict the elastoplastic constitutive relation of a tailor-tempered 22MnB5 sheet. (June 2022) - Tang, Bingtao; Li, Qianchi; Wang, Qingfeng; Guo, Ning; Meng, Xiangbin; Shi, Yanbin; Su, Hangqi; Lin, Liyuan
Abstract: A novel modification of Weng's secant approach to model the elastoplastic stress-strain response of tailor-tempered 22MnB5 steel with heterogeneous material properties when subjected to plastic deformation is described. In the tailored tempering process (TTP) of high-strength boron-manganese steel, different distributions of mechanical properties in the same component can be realized. The elastoplastic constitutive relation is an urgent issue when developing components with customized material properties. The capabilities of classical mixture rule methods and improved homogenization methods to describe the mechanical behavior of inhomogeneous products containing various volume fractions of constituent phases are extensively studied. Weng's secant model is modified by using the exponential function instead of the power law relation to calculate the flow stress of tailor-tempered 22MnB5 steel. To correctly predict the higher hardness of the bainite around martensite than that inside the bainite structure, which is due to plastic deformation of the surrounding local bainite induced by the volume expansion accompanying martensite transformation, the phase boundary considering the hardening of surrounding local bainite is introduced into the secant model. Furthermore, Vickers hardness parameters instead of phase volume control parameters are used in the modified secant method. The predictability of the overall response obtained using the novel micromechanical-based secant method shows good agreement with experimentally obtained elastoplastic deformation behaviors. Graphical Abstract: ga1 Highlights: Phenomenological methods, homogenization methods and the RVE method are comparatively studied. Flow stress of tailor-tempered 22MnB5 steel can be improved by using the exponential function. Considering the effect of the phase boundary can improve the prediction of the heterogeneous material response. Using the Vickers hardness-related factors can significantly enhance the predictability of stress-strain curves. The novel analytical method can be applied to predict the stain-hardening behavior of dual-phase steels.